2018
DOI: 10.3897/mbmg.2.24262
|View full text |Cite
|
Sign up to set email alerts
|

Estimating fish alpha- and beta-diversity along a small stream with environmental DNA metabarcoding

Abstract: Environmental DNA (eDNA) metabarcoding has been increasingly applied to biodiversity surveys in stream ecosystems. In stream networks, the accuracy of eDNA-based biodiversity assessment depends on whether the upstream eDNA influx affects downstream detection. Biodiversity assessment in low-discharge streams should be less influenced by eDNA transport than in high-discharge streams. We estimated α- and β-diversity of the fish community from eDNA samples collected in a small Michigan (USA) stream from its headwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
7
51
1
Order By: Relevance
“…We found that pairwise beta diversity (Sørensen dissimilarity) at the local scale was similarly assessed by the two methods, which is congruent to findings by Li et al (). Despite differences among sites in Sørensen dissimilarity, the turnover component (i.e., species replacement) contributes more to the dissimilarity than nestedness for both methods but is even more pronounced for eDNA than kicknet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that pairwise beta diversity (Sørensen dissimilarity) at the local scale was similarly assessed by the two methods, which is congruent to findings by Li et al (). Despite differences among sites in Sørensen dissimilarity, the turnover component (i.e., species replacement) contributes more to the dissimilarity than nestedness for both methods but is even more pronounced for eDNA than kicknet.…”
Section: Discussionsupporting
confidence: 91%
“…In near future, the forthcoming design and use of EPT-specific primers or the completion of EPT sequence references should reduce the current drawbacks of eDNA methods regarding taxonomic identification. For eDNA, we found a positive relationship between richness and discharge, which was not the case for kicknet data and could be attributed to eDNA integrating biodiversity detection across space due to downstream transport (Deiner & Altermatt, 2014;Li et al, 2018;Pont et al, 2018). Alternatively, richness indeed increased with discharge (i.e., downstream), but the slightly suboptimal sampling period (summer) and the simplified kicknet protocol we used was an inappropriate technique for sampling larger streams, and thus obscured the relationship.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the spatial community variance observed in other eDNA studies indicated that β‐diversity does not increase as a function of distance (up to 12 km) in a stream (Deiner et al, ), but does increase with distance in a highly dynamic marine habitat (O’Donnell et al, ). Li, Evans, et al () also observed that the β‐diversity of fish communities based on Jaccard distance (i.e., incidence data) between sampling sites is correlated with the sampling distance along the stream.…”
Section: Discussionmentioning
confidence: 94%
“…Encouragingly, Harper et al () demonstrated that Triturus cristatus (great crested newt) detection via metabarcoding with no threshold is equivalent to qPCR with a stringent detection threshold. eDNA metabarcoding has also been applied to large‐scale investigations of spatial or temporal variation in marine and freshwater communities, with some studies indicating that communities can be distinguished from 100 m to 2 km due to stream discharge or tidal patterns (Civade et al, ; Kelly, Gallego, & Jacobs‐Palmer, ; Li, Evans, et al, ; O’Donnell et al, ; Port et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Describing and explaning temporal and geographical variation in components of diversity is a mainstay of community ecology (Dornelas et al, 2014; Li et al, 2018; Magurran, 2013). α‐diversity can be calculated for the sampled community scale (be that a location or point in time), which has made its statistical analysis relatively straightforward.…”
Section: Discussionmentioning
confidence: 99%